Research Progress on the Potential Pathogenesis of Persistent Postural–Perceptual Dizziness - Chen Qin; Ruyi Zhang; Zhihui Yan (Brain and Behavior)
ABSTRACT Introduction Persistent postural–perceptual dizziness (PPPD) is the most prevalent chronic functional dizziness in the clinic. Unsteadiness, dizziness, or non‐spinning vertigo are the main symptoms of PPPD, and they are typically aggravated by upright posture, active or passive movement, and visual stimulation. The pathogenesis of PPPD remains incompletely understood, and it cannot be attributed to any specific anatomical defect within the vestibular system. Consequently, there is no objective examination method for the disease, and the diagnosis primarily depends on the symptoms of the patient, which lack specificity. Methods To better understand the pathogenesis of PPPD and to aid in the development of novel diagnostic strategies and therapies, we conducted a comprehensive narrative review of the relevant literature. We performed a search for literature in PubMed using the following search phrases: “persistent postural–perceptual dizziness” OR “PPPD” OR “chronic subjective dizziness” OR “functional dizziness” OR “space‐motion discomfort” OR “visual vertigo” OR “phobic postural vertigo.” The reference list of relevant studies was also screened. The search was limited to publications in English, and the final references were selected based on their relevance to the scope of this review. Results This review summarizes recent studies that have investigated the pathogenesis of PPPD. It is traditionally assumed that PPPD may result from altered postural control strategies, cortical integration of threat assessment and spatial orientation, or abnormal integration of multi‐sensory information. Recent studies have shown that the brain structure, activity, structural connectivity, and even cerebral perfusion of patients with PPPD differ from those of healthy individuals. Furthermore, PPPD patients are different from healthy individuals in spatial navigation ability, vestibular perception thresholds, central sensitization, and oxidative stress. These findings provide additional anatomical and behavioral insights into the pathogenesis of PPPD, suggesting that PPPD may arise from shifts in the interactions among emotional, visuo‐vestibular, and sensorimotor networks. Conclusion Understanding the complex pathogenesis of PPPD is crucial for the development of novel therapeutics against PPPD. Following the existing findings, our review suggests directions for future research.